Life satisfaction and internet and screen use among older adults in Spain - Renobell, Victor; Gómez-Ponce, Mariela; Fuentes-de-Frutos, Silvia (Acciones e Investigaciones Sociales, 2025)
The use of screens and the use of the Internet has an essential effect on the quality of life of older adults, however, there is a lack of studies that reflect how this use affects life satisfaction. This study investigates the relationships between Internet use and life satisfaction among older adults and exploits the mediating role of social interaction both on and off the Internet. 1274 participants aged 68 years (732 women and 542 men). Among the respondents, 54% were people who attended senior centers (688 people), and the rest were people who did not attend senior centers. The results indicated that Internet use is related to life satisfaction among older adults and that social interaction outside the Internet mediated Internet use. Our findings suggest that Internet use could improve the lives of older adults by encouraging offline social interaction. Therefore, society should create environments to help older adults socialize with virtual society to enhance offline social interaction.
Keywords: Internet use; Screen use; life satisfaction; social interaction; older adults; Spain